Comparison of the Effectiveness of Levofloxacin Eye Drop 0.5% and Povidone-Iodine 2.5% Against Conjunctival Normal Flora Bacterial Colonies in Intraocular Preoperative Procedures - Petty Purwanita; Okta Kurniawan Saputra; Erial Bahar; Nurmalia Purnama Sari (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2023)
Introduction: Endophthalmitis is the most severe ocular complication and often causes blindness. The incidence of endophthalmitis varies depending on the type of surgery performed, from 0.082% to 0.32%. The use of povidone-iodine and topical antibiotics on the conjunctiva has been reported to reduce the likelihood of postoperative infection. This study aimed to compare the effectiveness of levofloxacin ED 0.5% with povidone-iodine 2.5% in reducing the normal bacterial flora of the conjunctiva in intraocular preoperative procedures. Methods: Clinical trial experimental studies. A total of 34 research subjects participated in this study. The research subjects were grouped into treatment groups of 0.5% levofloxacin and 2.5% povidone-iodine. Analysis of differences in the number of bacterial colonies was carried out with the help of bivariate SPSS software. Results: Treatment with levofloxacin 0.5% eye drop was able to reduce the number of colonies by 78.11%, while treatment with povidone-iodine 2.5% was able to reduce the number of colonies by 68.57%. Conclusion: Levofloxacin 0.5% eye drop is superior in reducing the number of conjunctival bacterial colonies in intraocular preoperative procedures compared to 2.5% povidone-iodine.